Eksterminasi Hoaks Melalui “3S” Berbasis al-Qur'an - Faldiansyah, Iqrom; Amantha, Bimma (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Today, the problem that arises due to the increase in social media users is the number of hoaxes that are widespread around us. Suppressing hoaxes on social media can be categorized as very difficult. Because the phenomenon that occurs in society assumes that hoax is a trivial matter. So that, the spread of hoaxes through social media has become a common thing in everyday life. This paper uses a literature study method to see how solutions can be made at the personal level to deal with hoaxes. The concept offered is